Design and construction of a robotic solution for the University Rover Challenge (URC) (2017)
The project documented here, designed a solution in robotics that will solve tasks presented in the University Rover Challenge. An important group of tasks demand the construction of a robotic actuator to aid astronauts in a simulated Mars exploration mission. This work shows the design process for the first prototype of the robotic arm subsystem for the 2016 competition. The process concluded with the construction of two serial manipulators. Both were specifically designed for the tasks required by the competition. The first manipulator was specially built to collect tools in the floor outdoors. It was also built to hold the forces of tools made for digging and measuring temperature and humidity 10 cm deep. This arm has 3 degrees of freedom (DOF). The second manipulator was designed and mounted to solve more dexterous tasks, such as: unscrewing a DIN connector and screwing back again, pouring gasoline in a tank, connecting a carabiner to a wagon, among others. This arm has 7 DOF. The second arm uses parts of the first, given that changing configuration between tasks is allowed.